Botanical environments - Corwin, Elizabeth Jane, author; Hendry, Kenneth, advisor; Berland, John C., committee member; Crow, Mary, committee member (Colorado State University. Libraries, 1977)
In creating an environment for botanical life, I have used clay and plants which are both harmonious and complimentary to each other. The milieu created can be directly associated with my close personal involvement with nature. My forms clearly state a respect for plants and nature's geological formations, such as mountains, rocks and the effects of erosion. I feel strongly that I have conveyed my aesthetic interpretation of these natural forms and processes, I felt clay to be the most versatile and appropriate medium because of its plasticity, tactile qualities and color both in the wet and fired states. Wanting to compliment the oranges, reds and browns I found in the local geology, I became involved with unglazed clays using a variety of experimental firing techniques. Emphasis, therefore, was placed upon the natural beauty and color of the clay. As a result of my using unglazed clays, I was able to achieve the harmony between the plant and the environment that I sought. My clay surface echoed the softness I found in plant forms. During the exhibit, it became obvious to me that I had failed to create the variation in scale which had been initially intended. A contrast between very small and very large proportions would have added to the overall effect. However, I feel strongly that in the future these scale proportions will be resolved when I channel my efforts into creating exterior environments.
Keywords: Vases; Flowerpots; Plants in art